1990
DOI: 10.1007/bf01871669
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the water channels in the internodal cells ofNitellopsis

Abstract: The hydraulic resistance was measured on internodal cells of Nitellopsis obtusa using the method of transcellular osmosis. The hydraulic resistance was approximately 2.65 pm-1 sec Pa, which corresponds to an osmotic permeability of 101.75 microns sec-1 (at 20 degrees C). p-Chloromercuriphenyl sulfonic acid (pCMPS) (0.1-1 mM, 60 min) reversibly increases the hydraulic resistance in a concentration-dependent manner. pCMPS does not have any effect on the cellular osmotic pressure. pCMPS increases the activation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…At that time, and in contrast to what had been established in erythrocyte and kidney membranes, it was commonly assumed that water flow across the lipid moiety of plant membranes would be sufficient to take care of all cellular needs. However, aqueous channels in plant membranes had been discussed more than 25 years before (3), and functional evidence had been provided by a laboratory (20). It has been argued that the discovery of aquaporins did not revolutionize the biophysical basis of plant water relations (17), and this may well be true.…”
Section: Water Channels: a Revolutionary Discovery?mentioning
confidence: 99%
“…At that time, and in contrast to what had been established in erythrocyte and kidney membranes, it was commonly assumed that water flow across the lipid moiety of plant membranes would be sufficient to take care of all cellular needs. However, aqueous channels in plant membranes had been discussed more than 25 years before (3), and functional evidence had been provided by a laboratory (20). It has been argued that the discovery of aquaporins did not revolutionize the biophysical basis of plant water relations (17), and this may well be true.…”
Section: Water Channels: a Revolutionary Discovery?mentioning
confidence: 99%
“…Until recently, we were ignorant of the existence of proteins facilitating water movement [1,2], although the existence of proteinaceous water channels in plants had been suggested long ago, and received strong experimental support a decade ago [3,4]. The discovery of a family of genes encoding these protein channels, now known as aquaporins (AQPs), had been anticipated in principle by the earlier studies because water permeability, at least in some tissues and cells, has characteristics that cannot be explained if the lipid membrane is the sole barrier to water exchange (for reviews see [5][6][7][8]).…”
Section: Introductionmentioning
confidence: 99%
“…The biophysical evidence for this in higher plants has lagged behind the molecular work, but recent studies have shown that biophysical characteristics of water transport are consistent with water flow occurring predominantly through channels in some membranes. This evidence includes the following: (a) the ratio of osmotic to diffusional water permeability is greater than unity (Niemietz and Tyerman, 1997); (b) the activation energy is low (Maurel et al, 1997b; Niemietz and Tyerman, 1997); and (c) water permeability is sensitive to sulfhydryl reagents, in particular HgCl 2 (Maurel et al, 1997b; Niemietz and Tyerman, 1997).In the membranes of intact giant charophyte cells, high diffusional water permeability, low activation energy, and inhibition by sulfhydryl reagents have been well established (Wayne and Tazawa, 1990;Henzler and Steudle, 1995;Steudle and Henzler, 1995;Tazawa et al, 1996; Schü tz and Tyerman, 1997). The frictional interactions between the transport of water and highly permeant molecules (Tyerman and Steudle, 1982;Steudle and Henzler, 1995; Hertel and Steudle, 1997) are also indicative of water movement through aqueous pores in the membranes of characean cells.…”
mentioning
confidence: 99%
“…In the membranes of intact giant charophyte cells, high diffusional water permeability, low activation energy, and inhibition by sulfhydryl reagents have been well established (Wayne and Tazawa, 1990;Henzler and Steudle, 1995;Steudle and Henzler, 1995;Tazawa et al, 1996; Schü tz and Tyerman, 1997). The frictional interactions between the transport of water and highly permeant molecules (Tyerman and Steudle, 1982;Steudle and Henzler, 1995; Hertel and Steudle, 1997) are also indicative of water movement through aqueous pores in the membranes of characean cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation